MENUMBUHKAN SIKAP KEWIRAUSAHAAN SEJAK USIA DINI - Melda Darys Pesona; Nuru Annissa; Puput Prila Santika (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2024)
Entrepreneurship education must start from an early age. It is during this period that the role of parents is very necessary in shaping their life patterns, namely by instilling religious moral values, motivating them to study diligently and also using methods through play and reflection so that they hope that when they are adults they can become good people. who will be successful in the future. For this reason, the role of the father as head of the family must be able to support the role of the mother whose main task is to care for and educate children so that an entrepreneurial spirit can be fostered from an early age. The family plays a very big role in instilling an entrepreneurial spirit from an early age by involving the cooperation of both parents. The aim of this research is to describe what entrepreneurial skills should be given to children from an early age and to find out how children learn entrepreneurship. This research method is a literature study method. The results of collecting journals related to the title are entrepreneurial skills that can be introduced from an early age, namely the ability to do business based on their interests and hobbies. Children are able to learn business if parents guide children to think about how manage the business/business in a planned manner. Teachers and parents always act as facilitators so that they can note children's interests and talents.